Development of New Algorithm for Communication Networks Reliability Based on Tie Set Method Combined with a Modified Flooding Algorithm - Musaria Karim Mahmood (Tikrit Journal of Engineering Sciences, 2013)
This paper presents a new method to calculate the network reliability based on the use of flooding routing algorithm. Tie Set (TS) method is one of probabilistic reliability method, is combined with flooding technique to generate an efficient new method to estimate reliability. The proposed method can be generalized to be active with others reliability methods such as Cut Set, and Enumeration methods. TS method depends on two factors: finding the TS paths and the inclusion-exclusion expansion equations. A modified flooding algorithm is used to generate the group of TS paths which is then used to find the reliability. It will be demonstrated by a case experiment the simplicity and effectiveness of the flooding technique to generate paths between a pair of nodes in a graphical representation of a communication network.